2014
DOI: 10.1002/ccd.25391
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity of brachial versus femoral vein injection of agitated saline to detect right‐to‐left shunts with Transcranial Doppler

Abstract: The sensitivity of TCD for detection of RLS is increased when agitated saline injections are performed through the femoral vein. In patients with a high clinical suspicion for RLS, low TCD grades obtained with traditional brachial venous access should be interpreted with caution. When possible, a repeat study using femoral venous access may be considered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 8 publications
0
8
0
Order By: Relevance
“…Hammerstringl et al found that the Helex device is an independent risk factor for residual shunting . Von Bardeleben et al also described significant differences of closure rates between Helex and Amplatzer devices of larger size .…”
Section: Discussionmentioning
confidence: 99%
“…Hammerstringl et al found that the Helex device is an independent risk factor for residual shunting . Von Bardeleben et al also described significant differences of closure rates between Helex and Amplatzer devices of larger size .…”
Section: Discussionmentioning
confidence: 99%
“…In our study there were 4 patients whohadsevere platypnea-orthodeoxia despite having a grade3R to L shunt by TCD, which represents a small amount of blood flow. It is possible that these patientshavegreater shunting from the inferior vena cava andaTCD with agitated saline injection from the legmayhaveproducedahighershuntgrade [ 28].…”
Section: ± ±mentioning
confidence: 99%
“…Venous blood enters the RA via the superior vena cava (SVC), and directly traverses the tricuspid valve, whereas femoral venous blood enters into the RA via the inferior vena cava (IVC) and is directed towards the atrial septum and is therefore more likely to pass through the PFO if present ( Figure 6). [50][51][52] Since TCD, TTE and TOE are all relatively similar in the way they detect a RLS (i.e. they require the agitated saline to pass through the PFO), it is likely that change in injection site would also increase sensitivity when using either TTE or TOE, which has been demonstrated in studies by Gin 49 and Hamann.…”
Section: And Thementioning
confidence: 99%